The Short-Term Reliability of Metaphors as an Assessment Method - Wegner, Elisabeth; Burkhart, Christian; Nückles, Matthias (Frontiers in Education, 2021)
Metaphors are assumed to be a means of accessing implicit aspects of cognition. Metaphors, therefore, have been increasingly used in educational science as an innovative tool to examine a broad range of constructs. However, there are both empirical findings and theoretical considerations suggesting that metaphors are also by experiences that are salient just in the moment of production of the metaphor. Therefore, we examined in a sample of N = 95 students and professionals whether the metaphors of learning and the underlying conceptualization of learning that influence whether students adopt a deep or a surface approach in learning remained stable across three weeks. Results showed that although the sources on which the metaphors drew were subject to change, the underlying conceptualization of learning remained stable. However, there were no differences in the stability of metaphors in both groups. It be can concluded, therefore, that metaphors can be used as an indicator for underlying constructs such as the understanding of learning.